4D characterisation of void nucleation, void growth and void coalescence using advanced void tracking algorithm on in situ X-ray tomographic data - Azman, M.A.; Bourlot, C. Le; King, A.; Fabrègue, D.; Maire, E. (Elsevier, 2022)
An advanced tracking algorithm based upon 4D X-ray tomographic data was developed to enable a more robust and full field approach to ductile damage characterisation. By following each individual void, the three ductile damage mechanisms (void nucleation, void growth and void coalescence) could be separated and be studied in more detail, with enriched 4D information available for each of the three damage mechanisms. Here, a successful application of the developed tracking algorithm on a pure iron sample is presented. Two different notch geometries were chosen for the demonstration of analysis technique to further study the influence of triaxiality on ductile damage.